Chocolate Terahertz Fresnel Lens - Surma, Mateusz; Komorowski, Paweł; Neneman, Maciej; Siemion, Agnieszka (Photonics Letters of Poland, 2020)
Recent enormous development of 3D printing techniques gave the possibility of precise manufacturing of designed optical structures. This paper presents designing, manufacturing and the results obtained for chocolate Fresnel lens. Chocolate, similarly to wax, can be melted and used in the 3D printed form to create a terahertz (THz) optical element. Parameters of the chocolate lens are compared with the one made of wax. In simple applications both materials can be used as a cost-effective alternative for conventional optical materials used for THz range of radiation. Both lenses have been designed and compared for 140 GHz. Full Text: PDF References M. Naftaly, R.E. Miles, and P.J. Greenslade, "THz transmission in polymer materials — a data library", Joint 32nd International Conference on Infrared and Millimeter Waves and the 15th International Conference on Terahertz Electronics, 819-820 (2007). CrossRef S. Firoozabadi, F. Beltran-Mejia, A. Soltani, D. Jahn, S.F. Busch, J.C. Balzer, and M. Koch, "THz transmission blazed grating made out of paper tissue", 42nd International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 1-2 (2017). CrossRef D. Headland, W. Withayachumnankul, M. Webb, H. Ebendorff-Heidepriem, A. Luiten, and D. Abbott, "Analysis of 3D-printed metal for rapid-prototyped reflective terahertz optics", Optics express 24(15), 17384-17396 (2016). CrossRef S.F. Busch, M. Weidenbach, M. Fey, F. Schäfer, T. Probst, and M. Koch, "Optical Properties of 3D Printable Plastics in the THz Regime and their Application for 3D Printed THz Optics", Journal of Infrared, Millimeter, and Terahertz Waves 35(12), 993-997 (2014). CrossRef C. Jördens, and M. Koch, "Detection of foreign bodies in chocolate with pulsed terahertz spectroscopy", Optical Engineering 47(3), 037003 (2008). CrossRef A.D. Squires, E. Constable, and R.A. Lewis, "3D Printed Terahertz Diffraction Gratings And Lenses", Journal of Infrared, Millimeter, and Terahertz Waves 36(1), 72-80 (2015). CrossRef W. D. Furlan, V. Ferrando, J. A. Monsoriu, P. Zagrajek, E. Czerwińska, and M. Szustakowski, "3D printed diffractive terahertz lenses", Optics letters 41(8), 1748-1751 (2016). CrossRef X. Wei, C. Liu, L. Niu, Z. Zhang, K. Wang, Z. Yang, and J. Liu, "Generation of arbitrary order Bessel beams via 3D printed axicons at the terahertz frequency range", Applied optics 54(36), 10641-10649 (2015). CrossRef S. Banerji, and B. Sensale-Rodriguez, "3D-printed diffractive terahertz optical elements through computational design", Micro-and Nanotechnology Sensors, Systems, and Applications XI 10982, 109822X, International Society for Optics and Photonics (2019). CrossRef M. Surma, I. Ducin, P. Zagrajek, and A. Siemion, "Sub-Terahertz Computer Generated Hologram with Two Image Planes", Applied Sciences 9(4), 659 (2019). CrossRef A. Siemion, P. Komorowski, M. Surma, I. Ducin, P. Sobotka, M. Walczakowski, and E. Czerwińska, "Terahertz diffractive structures for compact in-reflection inspection setup", Optics Express 28(1), 715-723 (2020). CrossRef E.R. Brown, J.E. Bjarnason, A.M. Fedor, and T.M. Korter, "On the strong and narrow absorption signature in lactose at 0.53THz", Applied Physics Letters 90(6), 061908 (2007). CrossRef M. Bernier, F. Garet, and J. L. Coutaz, "Determining the Complex Refractive Index of Materials in the Far-Infrared from Terahertz Time-Domain Data", Terahertz Spectroscopy-Cutting Edge Technology, Intech-Open Science (2017). CrossRef E.Hecht, Optics 5th global ed.(Boston, Pearson Education 2017). DirectLink